Dataset VR (virtual reality) laboratorium komputer BRIN 2 di Repositori Ilmiah Nasional (RIN) - Herdianto, Arvy; Prasetyadi, Abdurrakhman; Hadi, Angga Arvianto (BACA: Jurnal Dokumentasi dan Informasi, 2024)
The rapid advancement of animation and 3D modeling technology, particularly in virtual reality (VR), has significantly transformed digital interactions. This article discusses the application of VR in computer laboratory simulations for research, experimentation, and data analysis. VR offers interactive 3D visualization, allowing users to view objects and spaces from various perspectives. The research method employed photogrammetry techniques at the BRIN Science and Technology Laboratory in Bandung to gather data. The collected data was then processed using Blender and Unity software, resulting in high-quality 3D models. The VR Lab Computer dataset from BRIN consists of 31 files, including 16 images and 15 3D object models that can be accessed through specific applications. The visualizations produced provide an accurate representation of the laboratory space, equipment, and tools available. The findings of this research indicate the significant potential of VR in education and research, as well as benefits for individuals with physical or geographical limitations. Thus, VR not only enhances the learning experience but also improves the efficiency of repeating experiments.